2021
DOI: 10.3390/ani11082335
|View full text |Cite
|
Sign up to set email alerts
|

Human-Dog Relationship during the First COVID-19 Lockdown in Italy

Abstract: The SARS-CoV2 pandemic forced an abrupt interruption of social contacts and interpersonal affective relationships all over the world, according to national directives. Many considerable inconveniences occurred with important repercussions also on the emotional state of people and their pets. We carried out a national survey to evaluate the human-dog relationship in a social isolation context using an adapted version of Monash Dog Owner Relationship Scale, the perception of the dogs’ discomfort by their human o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 62 publications
3
24
1
Order By: Relevance
“…Studies have reported an increase in dogs displaying behaviours indicative of SRBs during the COVID-19 Pandemic in Spain [ 53 ] and Italy [ 54 ], however a comparable study in the UK demonstrated a significant decrease in dogs exhibiting such behaviours during the first COVID-19 lockdown [ 55 ]. This was postulated to be the result of a four-fold increase in the number of owners not leaving their dogs alone during 2020 [ 21 ] with the authors citing these changes in dog management having the potential for an increased likelihood of dogs developing SRBs as COVID-19 restrictions ease [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported an increase in dogs displaying behaviours indicative of SRBs during the COVID-19 Pandemic in Spain [ 53 ] and Italy [ 54 ], however a comparable study in the UK demonstrated a significant decrease in dogs exhibiting such behaviours during the first COVID-19 lockdown [ 55 ]. This was postulated to be the result of a four-fold increase in the number of owners not leaving their dogs alone during 2020 [ 21 ] with the authors citing these changes in dog management having the potential for an increased likelihood of dogs developing SRBs as COVID-19 restrictions ease [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are somewhat at odds with those of a previous survey that found approximately 50% of veterinarians reported their clients were concerned about potential of SARS-CoV-2 transmission with their pets [ 41 ]. In Italy, research has also shown that 28% of dog owners altered their behavior during the early stages of the COVID-19 pandemic by cleaning their dogs following walks and ceasing participation in sporting activities [ 42 ]. Education was the key demographic variable that impacted owners’ perception of zoonotic transmission of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…This apparently amazing data should be considered with caution, since adoption is a complex phenomenon, affected by many factors, besides training per se, including appearance, social interaction with the adopter and personality [ 29 , 30 ], as well as the need for humans to improve their social and emotional wellbeing. Accordingly, although there is no significant year effect between dogs’ age and 2015–2020 period (One-way ANOVA: F (5,18) = 0.2465, p = 0.9362), our data showed an overall increase of adoptions in 2020, compared to the previous years, thus suggesting that, under stressful situations, such as that experienced during the forced lockdown, caused by SARS-CoV2 pandemic, humans might require to establish an emotional osmosis with companion animals to get pleasure from them [ 31 ]. Thus, to give a reliable support to our findings, more accurate studies, which deal with as many adoption-related factors as possible, are mandatory.…”
Section: Discussionmentioning
confidence: 85%